Waterproof lithium metal anode enabled by cross-linking encapsulation - Xiao, Ye; Xu, Rui; Yan, Chong; Liang, Yeru; Ding, Jun-Fan; Huang, Jia-Qi (Science bulletin, 2020)
[Display omitted] Lithium (Li) metal is considered as the ultimate anode choice for developing next-generation high-energy batteries. However, the poor tolerance against moist air and the unstable solid electrolyte interphases (SEI) induced by the intrinsic high reactivity of lithium bring series of obstacles such as the rigorous operating condition, the poor electrochemical performance, and safety anxiety of the cell, which to a large extent hinder the commercial utilization of Li metal anode. Here, an effective encapsulation strategy was reported via a facile drop-casting and a following heat-assisted cross-linking process. Benefiting from the inherent hydrophobicity and the compact micro-structure of the cross-linked poly(vinylidene-co-hexafluoropropylene) (PVDF–HFP), the as-encapsulated Li metal exhibited prominent stability toward moisture, as well corroborated by the evaluations both under the humid air at 25 °C with 30% relative humidity (RH) and pure water. Moreover, the encapsulated Li metal anode exhibits a decent electrochemical performance without substantially increasing the cell polarization due to the uniform and unblocked ion channels, which originally comes from the superior affinity of the PVDF–HFP polymer toward non-aqueous electrolyte. This work demonstrates a novel and valid encapsulation strategy for humidity-sensitive alkali metal electrodes, aiming to pave the way for the large-scale and low-cost deployment of the alkali metal-based high-energy-density batteries.